1998
DOI: 10.1165/ajrcmb.19.3.3183
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Inhaled Ozone Concentration to Acute Tracheobronchial Epithelial Injury, Site-specific Ozone Dose, and Glutathione Depletion in Rhesus Monkeys

Abstract: Acute pulmonary epithelial injury produced by short-term exposure to ozone varies by site within the tracheobronchial tree. To test whether this variability is related to the local dose of ozone at the tissue site or to local concentrations of glutathione, we exposed adult male rhesus monkeys for 2 h to filtered air or to 0.4 or 1.0 ppm ozone generated from 18O2. Following exposure, lungs were split into lobes and specimens were selected by microdissection so that measurements could be made on airway tissue of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 23 publications
2
38
1
Order By: Relevance
“…A number of investigators have observed statistically significant increases in alveolar macrophages (AM), protein, albumin, total cell counts, and polymorphonuclear monocytes (PMNs) numbers in BALF and bronchiolar epithelium of rodents, dogs, and monkeys at various time points following acute exposures to 0.2 ppm O 3 (Freed et al, 1999;Kleinman et al, 1999;Oosting et al, 1991;Plopper et al, 1998). Both monkeys and ferrets appear to be more sensitive to O 3 -induced inflammatory cell infiltration and airway epithelial injury than rodents (Sterner-Kock et al, 2000).…”
Section: Lung Structure and Cellularity Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of investigators have observed statistically significant increases in alveolar macrophages (AM), protein, albumin, total cell counts, and polymorphonuclear monocytes (PMNs) numbers in BALF and bronchiolar epithelium of rodents, dogs, and monkeys at various time points following acute exposures to 0.2 ppm O 3 (Freed et al, 1999;Kleinman et al, 1999;Oosting et al, 1991;Plopper et al, 1998). Both monkeys and ferrets appear to be more sensitive to O 3 -induced inflammatory cell infiltration and airway epithelial injury than rodents (Sterner-Kock et al, 2000).…”
Section: Lung Structure and Cellularity Changesmentioning
confidence: 99%
“…The most pronounced lesions occur in the centriacinar region which receives the largest O 3 dose (e.g. terminal and respiratory bronchioles in primates) (Plopper et al, 1998). Ciliated respiratory epithelium in the tracheobronchiolar region is damaged in a dose-dependent manner by repeated O 3 exposures 0.2 ppm (Castleman et al, 1980;Van Bree et al, 2001).…”
Section: Lung Structure and Cellularity Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both computer simulation studies of pulmonary O 3 reactions and experimental observations bear this out, since there is not a particularly "deep" penetration of O 3 and O 3 -mediated cell injury into the lung. The primary anatomic sites of O 3 reaction in the lungs (at environmentally relevant concentrations of 0.5 ppm or less) are the airway and nasal epithelium, with small conducting airways and bronchioles a preferred reaction site, rather than more distal parenchymal alveolar epithelial cell reactions (18,20,25). Even in still-developing primate infants, episodic O 3 exposure primarily affects the morphogenesis of tracheobronchial airways and damages airway epithelial cells in terminal and respiratory bronchioles (8).…”
mentioning
confidence: 99%
“…The axial dose distribution is different depending on the properties of the gases (Nodelman & Ultman, 1999); for example, chlorine was absorbed in upper airways and trachea, and ozone reached lower airways. Experiments were done to relate the concentration of ozone exposure and the epithelial injury in an asymmetric rhesus monkey lung (Plopper et al, 1998) and rat lung Joad et al, 2000). The distribution of tissue dose is dependent on axial dose distribution of gases in lungs, which is difficult to measure, so it is important to develop mathematical models of flow, diffusion, and reaction of reactant pollutants in the respiratory system.…”
mentioning
confidence: 99%